The possibility of global public Sociology - SAITO, Hiro (Institutional Knowledge at Singapore Management University, 2015)
In this paper, I revisit the debate on public sociologywithin the wider institutional context of higher education.Once ramifications of globalisation of highereducation are taken into account, institutional constraintsplaced on public sociology turn out to bemuch larger than previously thought: a) the institutionalisationof world university rankings reinforcesthe dominance of professional sociology over publicsociology and; b) the commercialisation and vocationalisationof higher education worldwide underminesthe discipline of sociology as a whole. At the sametime, however, globalisation of higher education facilitatesthe formation of transnational networks ofsociologists examining transnational social problems,ranging from marketisation to climate change. Theseemerging transnational networks are likely to serve asinfrastructures for sociologists to engage publics informulation and dissemination of research on transnationalsocial problems and thereby forge a sociologythat is simultaneously global and public.